IMPLEMENTING TOKEN-BASED AUTHENTICATION AND MODIFIED HASHING FOR IOT SECURITY - Rao, B Bamleshwar; Waoo, Akhilesh A (ShodhKosh: Journal of Visual and Performing Arts, 2024)
“Internet of Things” mainly refers to the information exchange between objects or devices through the Internet. It is an innovative technology based on advanced network information technologies such as computer technology and Internet technology and is also one of the main directions for the development and application of network information technology. The emergence and operation of the Internet of Things technology will greatly promote the enhancement of the degree of Informatization in related fields. In addition, it also has an important impact on the construction and management of smart cities, and smart hospitals and the upgrading and transformation of industrial production, and people’s daily lives. It also provides new ways and technical support for solving many bottlenecks that restrict social and economic development.